(untitled) (International Journal of Engineering and Computer Science, 2014)
Content based image Retrieval is an active research field in past decades. Against the traditional system where the images are retrieved based on the keyword search, CBIR system retrieve the images based on the visual content. The large numbers of images has posed increasing challenges to computer systems to store and manage data effectively and efficiently. This paper implements a CBIR system using different feature of images through four different methods, three were based on analysis of color feature and other one based on analysis texture feature using gabor wavelet coefficients of an image.